Basophil Count, Percentage of Basophil and Basophil Lymphocyte Ratio in Psychiatry Practice: Current Approaches and Future Directions - Mehmet Hamdi Orum (Journal of Contemporary Medicine, 2020)
It is an easy and inexpensive method to utilize hematologic parameters in cases where we cannot get clear information from the patients. The basophils are definitely involved in immunopathologic responses to parasites, and in this respect, there may be a relationship between parasitic infections and developmental disorders. In this study, we discussed the possible uses of basophil and related parameters.